Nueva peptona de origen vegetal como medio de cultivo para Bacterias y Hongos - Ceruzzi, Francisco (Revista Universidad de Guayaquil, 1998)
In this communication, a new culture medium for bacteria and fungi is prepared and described, using peptone obtained from enzymatic hydrolysis, either acid or alkaline, of tender leaves and stems of "alfalfa" (Medicago sativa L.) as a substrate.The techniques for preparing this new culture medium are detailed, the bacterial and fungal species that grow on it are mentioned, and growth characteristics are discussed, along with a comparative evaluation of proliferation with other culture media.It is concluded that "alfalfa" undoubtedly constitutes an optimal resource for the preparation of bacteriological and mycological culture media, given that it is a cosmopolitan plant that is easily obtainable, due to the large amount of nutritious substances it contains, the simplicity of medium preparation, and its low cost.